The role of psychosocial counselling in the lives of parents of children with neurodevelopmental disabilities treated at Tygerberg Academic Hospital - Witbooi, Lizzie Gladys (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil(Rehabilitation))--Stellenbosch University, 2013.